Non-carbapenem-producing carbapenem-resistant Pseudomonas aeruginosa in children: Risk factors, molecular epidemiology, and resistance mechanism - Lijun Yin; Lu Lu; Leiyan He; Gangfeng Yan; Guoping Lu; Xiaowen Zhai; Chuanqing Wang (Journal of Infection and Public Health)
Background: The investigation into risk factors, molecular epidemiology, and resistance mechanisms of carbapenem-resistant Pseudomonas aeruginosa (CRPA) in pediatric populations in China is currently inadequate. Methods: To assess epidemiology, molecular characteristics, and resistance mechanisms, virulence-associated genes were analyzed, alongside multi locus sequence typing (MLST), PCR, and qRT-PCR. Finding: Multivariate analysis identified prolonged hospitalization (OR: 1.026; 95 % CI: 1.004–1.049; P = 0.023) and increased exposure to enzyme inhibitor complex preparations (OR: 3.165; 95 % confidence interval [CI]: 1.113–8.999; P = 0.031) as independent risk factors for CRPA healthcare-associated infections (HAIs). Mortality rates were significantly higher in the HAI group compared to the non-HAI group (19.1 % vs. 6.0 %, P = 0.021). Analysis of virulence-associated gene combinations revealed 10 and 15 distinct profiles among HAI and non-HAI isolates, respectively, characterized by exoS−/exoU+ or exoS+ /exoU− genotypes, with no isolates exhibiting both exoS+ and exoU+ genotypes concurrently.Infections predominantly correlated with CC244, with a significantly greater occurrence in the HAI group (72.1 % vs. 46.3 %, P = 0.002). Antimicrobial susceptibility testing identified that both CC244 + and HAI isolates demonstrated elevated resistance across all tested antibiotics. Furthermore, low oprD expression was observed in 77.9 % of HAI isolates and 67.2 % of non-HAI isolates, while increased ampC production and mexB gene overexpression were infrequently detected (all P > 0.05). Conclusions: Prolonged hospital stays and an increased exposure to enzyme–inhibitor complex therapies were identified as independent risk factors for CRPA HAIs. CRPA demonstrated considerable genetic diversity, with STs predominantly represented by CC244, and virulence-associated genes have spread. The primary mechanism driving carbapenem resistance involved the downregulation of outer membrane porin protein oprD, accompanied by oprD mutation inactivation.